Quantifying day-to-day variability of O/N2 and its correlation with geomagnetic activity using GOLD - Martinez, Benjamin C.; Lu, Xian (Frontiers in Astronomy and Space Sciences, 2023)
We quantify the short-term (<30 day) variability of column O/N2 measured by GOLD from January 2019 to August 2022 for various geomagnetic activity conditions. We find enhanced variabilities at high latitudes during active (Kp ≥ 3.0) times and weak but statistically significant variabilities at low latitudes. For active times, the largest absolute variability of O/N2 ratio is 0.14 and the largest relative variability is 20.6% at ∼60.0°N in Fall, which are about twice those of quiet times. The variability at higher latitudes can be larger than that of lower latitudes by a factor of 5–8. We further quantify contributions of magnetospheric forcing to O/N2 variability in the Ionosphere-Thermosphere region by correlating O/N2 perturbations with Dst. During geomagnetic active times, positive correlations as large as +0.66 and negative correlations as large as −0.65 are found at high and low latitudes, respectively, indicative of storm-induced O and N2 upwelling at high latitudes and down welling at low latitudes. During quiet times, correlations between O/N2 perturbations and Dst become insignificant at all latitudes, implying a more substantial contribution from below. O/N2 variabilities maximize in Fall and decrease towards Summer, while correlations maximize in Spring/Summer and decrease in Winter/Spring, which may be related to seasonal variations of geomagnetic activity and mean circulation.